Parent and student perceptions of the science learning environment and its influence on student outcomes - Allen, Debra (Curtin University, 2003)
This thesis reports on the modification, validation and application of a classroom learning environment questionnaire. This thesis is distinctive in that parents' perceptions were utilised in conjunction with students' perceptions in investigating science classroom learning environments among Grade 4 and 5 students in South Florida. The What is Happening in this Class? (WIHIC) questionnaire was modified for young students and their parents. Data from samples of students and parents were analysed to check the reliability and validity of the modified questionnaires and to examine similarities and differences between parents' and students' perceptions of the learning environment. Associations between parents' and students' perceptions of the science learning environment and student outcomes (attitude and achievement) were also investigated in this study. Parents and students were interviewed to check further the validity and reliability of questionnaires and to enhance the richness of the quantitative findings. Interviews with parents and students, along with classroom observations, offered some insights into the quantitative findings. Data analyses supported the WIHIC's factorial validity, internal consistency reliability and ability to differentiate between the perceptions of students in different classrooms. Both students and parents preferred a more positive classroom environment than the one perceived to be actually present, but effect sizes for actual-preferred differences were larger for parents than for students.Associations were found between some learning environment dimensions (especially Task Orientation) and student outcomes (especially attitudes). Qualitative methods suggest that students and parents were generally satisfied with the classroom environment but that students would prefer more investigation while parents would prefer more teacher support. The study provides a pioneering look at how parents and students perceive the science learning environment and opens the way for further learning environment studies involving parents and students.